Down-regulation of TGF-β, VEGF, and bFGF in vascular endothelial cells of chicken induced by a brittle star (Ophiocoma erinaceus) extract - Saeed Ataei Kachooei; Roya Rahmani; Nasrin Zareh; Fatemeh Donyadideh; Saba Ataei Kachooei; Mohammad Nabiuni; Sajjad Yazdansetad (Heliyon, 2020)
Great attention has been focused on the discovery of anti-angiogenic natural and synthetic compounds to be finally used as or at least a part of the treatment of tumors. The marine ecosystems provide diversity in natural chemicals with the potential of being exploited as medicines in the treatment of diseases. Several studies have investigated Ophiuroids as a source of anti-tumor and anti-metastatic organisms. Here, we described the inhibitory effects of an ethanolic crude extract of brittle star (Ophiocoma erinaceus) on angiogenesis and the expression level of TGF-β, VEGF, and bFGF in chicken chorioallantoic membrane (CAM) as an experimental model. To do this 45 embryonated eggs were randomly divided into six groups including the control group, sham, three experimental groups and positive. The number and the length of vessels were calculated using ImageJ® software. The relative mRNA levels of the genes in different groups were evaluated by qRT-PCR method. Our study was suggestive of an anti-angiogenesis effect of brittle star ethanolic crude extract in a CAM model. The extract also showed a pharmacological effect of down-regulation of mRNA related to VEGF, TGF-β, and bFGF genes on chicken vascular endothelial cells. It was also showed that the observed inhibitory effect is with a dose-dependent manner in which the highest inhibitory effect belonged to the highest used dose. We indicated the anti-angiogenesis properties of the Persian Gulf brittle star. Further studies are needed in other aspects of the brittle star extract in the treatment of angiogenesis, hyperplasia, and cancers.